Ewolucja recepcji twórczości Josepha Conrada w Polsce - Przybysz, Kinga (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
In the essay author describes the way J. Conrad’s books were interpreted during decades by polish critics and readers. Author argues that reception of J. Conrad’s books was determined by the periods in which critics and readers lived. During war J. Conrad’s works were perceived as guides and psychical assistance. After World Word II critics divided into main two groups – one group maintained that J. Conrad’s conceptions were harmful and the other group pointed that J. Conrad’s books were important and carried universal meanings. Nowadays J. Conrad is still interpreted in very different ways. Author focuses only on Zdzisław Najder’s interpretations.